Pulmonary Valve Infective Endocarditis in an Adult Patient with Severe Congenital Pulmonary Stenosis and Ostium Secundum Atrial Septal Defect. (26th December 2010) - Lacalzada, Juan; Enjuanes, Cristina; Izquierdo, Maria Manuela; Barragán Acea, Antonio; De La Rosa, Alejandro; Laynez, Ignacio
Abstract : A hypertensive 76-year-old man with severe pulmonary valve stenosis (PVS) and recent initiation of haemodialysis was referred with fever, chills, and asthenia. One month prior, he had been admitted with similar symptoms. Transthoracic echocardiography (TTE) had shown a PVS and no valve vegetations were observed. Following discharge, he was readmitted with fever and blood cultures positive for Staphylococcus haemolyticus . A new TTE revealed two pulmonary valve vegetations and a previously undetected ostium secundum-type atrial septal defect (ASD), confirmed by transesophageal echocardiography. The clinical course was uneventful with intravenous antibiotic treatment and the patient was safely discharged. This is a case of pulmonary valve infective endocarditis (IE). The incidence of right-sided IE is on the rise due to the increased number of patients using central venous lines, pacing, haemodialysis and other intravascular devices. Pulmonary valve IE is extremely rare, especially in structurally normal hearts. The case reported here, presents a combination of predisposing factors, such as severe congenital PVS, the presence of a central venous catheter, and haemodialysis. The fact that it was an older patient with severe congenital PVS and associated with a previously undiagnosed ASD, is also an unusual feature of this case, making it even more interesting.